Analisis Efektivitas dan Efisiensi Program PAMSIMAS dalam Penyediaan Air Bersih di Dusun V Kampung Baru, Kampar Utara - Hamid, Ardiansyah; Yelmi, Harmi; Aga Wandana, Fajar (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2025)
The availability of clean water in the area of Dusun V Kampung Baru is very minimal. On average, the quality of well water in residents is yellowish, muddy and oily. To solve this problem, residents of Dusun V Kampung Baru received assistance from the PAMSIMAS clean water program from the government. Clean water facilities have been built and water has been distributed to homes in need. Therefore, an evaluation is needed in the implementation of this program, to determine the achievement of the objectives of this program. The evaluation indicators are seen from the aspects of the effectiveness and efficiency of the implementation of the PAMSIMAS program. This study uses descriptive qualitative data analysis, based on the results of observations and interviews with PAMSIMAS water customers. When viewed from the effectiveness indicator, the clean water program is quite effective for residents of Dusun V Kampugn Baru, because the program's objectives have been achieved, namely clean water has been obtained and has been distributed to residents' homes. Likewise, from the efficiency indicator, the implementation of the PAMSIMAS program is running efficiently. This is assessed from the construction of clean water facilities that are in accordance with the plan by utilizing existing human resources and optimizing available funds. With the evaluation of the PAMSIMAS clean water program, we can measure the achievement of the PAMSIMAS program objectives and also provide a picture of the implementation of PAMSIMAS in Dusun V Kampung Baru to date